Seafaring Archaeology of the East Coast of India and Southeast Asia during the Early Historical Period. (27th July 2017) - Tripati, Sila
The concept of trade in ancient India was quite different from modern times. In olden day's mariners, artisans, traders, Buddhist monks and religious leaders used to set sail together and this trend continued till the advent of modern shipping. The representation of art on the walls of the caves, stupas and temples enlighten us regarding their joint ventures, experiences and problems faced during the sea voyages. The finding of varieties of pottery, punch marked and Roman coins, Brahmi and Kharoshti inscriptions along the ports, trade centres and Buddhist settlements suggest the role played by them in maritime trade during the early historical period and later. Mariners of India were aware of the monsoon wind and currents for more than two thousand years if not earlier. Furthermore, the study shows that the maritime contact with Southeast Asian countries was seasonal and no changes of Southwest and Northeast monsoon have been noticed since then. This paper details the types of pottery, beads, cargo found at ports, trade routes and Buddhist settlements along the east coast of India and the role of monsoons in maritime trade. The impact of Buddhism on trade and society of the region are also discussed.